Avaliação in vitro do efeito da desnaturação térmica do colágeno e do tratamento com clorexidina da dentina na resistência adesiva - Silva, Marília Mota (2010)
The current adhesive systems promote an immediate and effective bond strength to dental substrates, however, over time, there may be a degradation of that process, impacting negatively on the maintenance of resistance values. Chlorhexidine digluconate (CHX) its widespread use in dentistry as an antimicrobial agent, however beyond acting disinfectant, it has been studied to maintain the stability of the bond strength. On the other hand, some authors have considered the hypothesis that the collagen fibers may not be as important for micromechanical union between dentin and composite resin, since there is evidence that the phosphoric acid itself can lead to a change in the structure molecular fibers, which can denature them. The aim of this study was evaluate the effect of thermal collagen denaturation and 2% chlorhexidine (CHX) application on resin-dentin bond strength in teeth restored with conventional adhesive. The study sample consisted of 30 human third molars, of which the dentin was exposed followed by phosphoric acid etching. The specimens were distributed in three main groups (CHX, thermal denaturation and control). Thermal denaturation consisted of immersion in water at 50ºC for 10 minutes. Control and thermal denaturation groups was costumarily restored and CHX group was treated with 2% chlorhexidine after acid etching and before bonding. The specimens were stored in distilled water at 37ºC for 24 hours or 6 months and then sectioned into sticks which were submitted to tensile bond testing at a crosshead speed of 1mm/min. The bond failure mode was observed by microscopy (40X). The results of the tensile bond test were expressed in MPa and analyzed with the tests of Kolmogorov-Smirnov, Levine, Snyder F, Tukey and Student t. In all groups bond strength decreased significantly over 6 months (p<0.05), but the loss of bond strength was smaller in the CHX group (16,08%) than in the control group (27,27%) and the thermal denaturation group (28,58%). The hybrid layer was extensively degraded over a period of 6 months. However, treatment with CHX reduced loss of bond strength in relation to controls. Thermal denaturation of collagen fibrils did not affect bond strength.